Physico-chemical properties of MTA and a novel experimental cement - Santos, A. D. [UNESP]; Moraes, J. C S [UNESP]; Araújo, E. B. [UNESP]; Yukimitu, K. [UNESP]; Valério Filho, W. V. [UNESP] (Wiley, 2005)
Aim: To evaluate the release of calcium ions, pH and conductivity of a new experimental dental cement (EC) and to compare them with those of mineral trioxide aggregate (MTA-Angelus). Methodology: Five samples of each cement were prepared using plastic tubes 1 mm in diameter and 10 mm long. Each sample was sealed in a test tube containing 10 mL deionized water which was analysed after 24, 48, 72, 96, 192, 240 and 360 h for pH, electrical conductivity and calcium release. The concentration of calcium ions was obtained through atomic absorption spectroscopy technique. The data were analysed statistically using the analysis of variance (ANOVA) and the Student's test (t-test). Results: The pH of the storage solutions was not affected by the material and the interaction of material with time (P > 0.05). However, the time of immersion was significant (P < 0.01) for both materials. For the electric conductivity and calcium release, the interaction of material with time was statistically significant (P < 0.01), indicating that EC and MTA-Angelus did not behave in a similar manner. Conclusions: The experimental cement released calcium and increased the pH of the storage solutions in a similar manner to MTA-Angelus. However, EC showed significantly higher calcium release than commercial MTA-Angelus after 24 h. © 2005 International Endodontic Journal.
Keywords: Electrical conductivity; Mineral trioxide aggregate; pH; Portland cement; Release of ions; biomaterial; calcium ion; mineral trioxide aggregate; tooth cement; unclassified drug; atomic absorption spectrometry; calcium transport; electric conductivity; physical chemistry; statistical analysis; statistical significance; structure analysis; Aluminum Compounds; Analysis of Variance; Calcium; Calcium Compounds; Dental Cements; Drug Combinations; Electric Conductivity; Hydrogen-Ion Concentration; Ions; Materials Testing; Oxides; Root Canal Filling Materials; Silicates; Spectrophotometry, Atomic